Processing and characterization of W23Mo23V17Cr8Ta7Fe22 and WMoVCrTa refractory high entropy alloys. (November 2021) - Das, Sujit; Robi, P.S.
Abstract: Refractory high entropy alloys (RHEAs) exhibit high strength, high hardness and stable microstructure over a wide range of temperatures. However, these alloys are also characterized by poor ductility. Total strain to failure of 6.2% at room temperature was observed in equiatomic WMoVCrTa RHEA. Attempts are made to improve the mechanical properties by altering the composition of existing RHEAs. This report presents the results of mechanical properties viz., room and elevated temperature properties of W23 Mo23 V17 Cr8 Ta7 Fe22 and WMoVCrTa RHEAs fabricated by mechanical alloying followed by vacuum arc melting. Both the arc melted alloys revealed presence of two Body-Centered Cubic (BCC) structured phases along with a small amount of intermetallic phase. The arc melted W23 Mo23 V17 Cr8 Ta7 Fe22 alloy exhibited compressive yield strength of 1688 MPa and an ultimate strain of 7.3% at room temperature whereas at 1000 °C the corresponding values were 1514 MPa and 10.6%. At 1000 °C the arc melted equiatomic WMoVCrTa alloy exhibited compressive yield strength of 785 MPa and an ultimate strain of 5.7%, whereas at 1200 °C the corresponding values were 941 MPa and 8.3%. Yield stress anomaly was observed for the two alloys at elevated temperatures. Both alloys possess high hardness at room temperature. The two RHEAs appear to be viable materials for high-temperature applications like gas turbine blades, combustion chamber lining, high-temperature coating, nuclear reactor walls, etc., due to their combination of high hardness, high strength and yield strain at elevated temperatures. Graphical abstract: Unlabelled Image Highlights: Alloys of W23 Mo23 V17 Cr8 Ta7 Fe22 and WMoVCrTa possess excellent high temperature strength and yield strain. Both alloys exhibit yield stress anomaly. Two alloys have high hardness. Both alloys contain two BCC phases and an intermetallic phase.